New data on the distribution of Red-breasted goose and Lesser white-fronted goose in the south of the Gydan Peninsula - Igor G. Korobitsyn; Oleg Yu. Tyutenkov (Acta Biologica Sibirica, 2023)
The Red-breasted goose Branta ruficollis (Pallas, 1769) and the Lesser white-fronted goose Anser erythropus (Linnaeus, 1758) are rare bird species nesting in the Arctic tundra zone of Eurasia usually in association with Peregrine falcons Falco peregrinus Tunstull, 1771. The Red-breasted goose, which has a vulnerable status according to the Red List of the International Union for Conservation of Nature (IUCN), currently has a positive population trend. The Lesser white-fronted goose with the same status, on the contrary, is declining in numbers. Both species are under the scrutiny of geese specialists. To identify the possible nesting of these species, suitable steep banks of the Indik'yakha River were surveyed in the south of the Gydan Peninsula. In 2019, six nesting aggregations of Red-breasted goose were discovered with a total number of 11 pairs in association with Peregrine falcons. In 2021, only two nesting localities with three pairs of geese were found in the same area, and in 2022 three localities each with a pair of geese. In addition, in 2022, three nesting sites of Lesser white-fronted goose were registered, also with a pair of birds in each place. In one case, the Lesser white-fronted goose and the Red-breasted goose nested in one place together. The new findings of their nesting are the southernmost nesting sites in the south of the Gydan Peninsula, providing important information for their conservation management and monitoring needs to continue.